Climate Shocks, Intimate Partner Violence, and the Protective Role of Climate-Resilience Projects - Amanda Guimbeau; Xinde James Ji; Nidhiya Menon (Institute of Labor Economics (IZA), 2024)
This study investigates the impact of climate change on intimate partner violence in Bangladesh and shows that policy can mitigate much if not all of the harmful consequences of climate shocks on women. Utilizing a novel dataset linking geo-referenced meteorological remote-sensed data with information on women's agency from the Bangladesh Demographic and Health Surveys, we find that dry shocks increase tolerance for intimate partner violence among women in poor and agriculture-dependent communities, amplifying existing social and environmental vulnerabilities. Climate resilience projects funded by the Bangladesh Climate Change Trust (BCCT), a domestic climate fund, mitigate the negative impacts of dry shocks, highlighting the important role of such initiatives in generate positive spillover effects in ameliorating the negative social impacts of changing climate. We show that impacts are mitigated as these projects enhance resilience in agriculture by reducing the effects of droughts on acreage and yield in rainfed areas. Our findings underline the role of targeted policy interventions in fostering climate adaptation and wellbeing.
Keywords: Q54; J16; O13; 330; climate change; women's agency; intimate partner violence; adaptation; mitigation; resilience; agriculture; Bangladesh